Last wishes - Schwab, Victoria (Schwab, Victoria. Everyday angel, 2015)
This time, guardian angel Aria must help Mikayla, who is under extra pressure to win a dance scholarship. But as the two girls become friends, Aria isn't even sure if she wants to earn her wings anymore.